Securing the Future of Copyright Users’ Rights in Canada - Al-Sharieh, Saleh (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2018)
The Copyright Act includes a set of copyright infringement exceptions that permit the unauthorized use of copyrighted works in order to serve public interest objectives. The Supreme Court of Canada liberally interpreted these exceptions as “users’ rights” by relying on the purpose of the Act, understood as a balance between the authors’ right to be rewarded for their works and the public interest in the dissemination and use of works. The utility of copyright balance to safeguard users’ rights is uncertain. The Act does not explicitly adopt “balance” as a purpose. National and international copyright law traditionally recognize the users’ side in the copyright law balance in copyright exceptions and limitations. And, in copyright law discourse, different stakeholders propose and defend conflicting forms of balance. Therefore, the paper argues that a human rights-based approach to copyright exceptions is more persuasive in justifying their interpretation as users’ rights. Copyright users’ rights mirror the content of the human rights to participate in culture, education, and freedom of expression, which Canada is obliged to implement as a State Party to the International Covenant on Economic, Social and Cultural Rights and International Covenant on Civil and Political Rights. The proposed approach would align the discourse with key elements of Canadian jurisprudence: (1) human rights as reinforcers of the rule of law; (2) international human rights law as an interpretive tool for Canadian courts; and (3) the need to interpret Canadian legislation in a manner that does not breach international obligations.